Peran Komitmen Organisasi Dalam Memediasi Pengaruh Job Demand dan Stres Kerja Terhadap Kinerja Karyawan dengan Percevied Organizational Support Sebagai Variabel Moderasi (Studi Kasus di Satuan Kerja Inspektorat Jenderal Kementerian XYZ) - Utomo, Agung Tri (Forum Kerjasama Pendidikan Tinggi, 2023)
The purpose of this study was to analyze the effect of job demand and work stress on organizational commitment. To analyze the effect of job demand, work stress and organizational commitment on employee performance. To analyze whether perceived organizational support can weaken the negative effect of job demand and work stress on employee performance. This study uses a quantitative approach with an explanatory design. The population in this study were all employees of the Inspectorate General of the XYZ Ministry. The sample method used is probability sampling, the sampling technique uses simple random sampling, so the sample size used in this study is 100 respondents. The data analysis method uses the Structural Equation Model (SEM) using the Smart PLS program version 3.2.9. The results of the study prove that job demand and work stress affect the organizational commitment of employees working at the Inspectorate General of the XYZ Ministry. Job demand, work stress and organizational commitment affect the performance of employees working at the Inspectorate General of the XYZ Ministry. Perceived organizational support cannot moderate the effect of job demand and work stress on performance of employees working at the Inspectorate General of the XYZ Ministry.